Effects of blood flow restriction moderate intensity interval training on aerobic and anaerobic capabilities and lower extremity performance in male college basketball players - Chen, L.; Zhang, Z.; Qu, W.; Huang, W.; Sun, J.; Duan, X.; Li, D. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This study investigated whether blood flow restriction moderate-intensity interval training (BFR-MIIT) could achieve or surpass the training effects of high-intensity interval training (HIIT) at lower training intensities. A total of 33 male college basketball players completed the trial and were randomly assigned to the BFR-MIIT group (n = 17) and the HIIT group (n = 16). Both groups performed the 4 × 4 "Norwegian" training method, with the BFR-MIIT group engaging in moderate-intensity training and the HIIT group in high-intensity training. Assessments included the Wingate Anaerobic Power Test, the multistage 20-meter shuttle run test, and tests of jumping ability (countermovement jump (CMJ), squat jump (SJ), and drop jump (DJ)), sprinting ability (30-meter sprint), and change of direction ability (505 test). Post-intervention, both the BFR-MIIT group (p < 0.001, ES=-1.199) and the HIIT group (p = 0.02, ES=-0.526) showed significant and equivalent improvements in VO2max. However, neither group significantly improved peak power (PP) or relative peak power (PP/kg). The BFR-MIIT group demonstrated superior improvements in lower extremity performance compared to the HIIT group in CMJ (p = 0.007; ES=-0.570), SJ (p < 0.001; ES=-0.537), DJ (p < 0.001; ES=-0.805), and the 505 test (p < 0.001; ES = 1.708). Additionally, across four measurements of the Rate of Perceived Exertion (RPE), the BFR-MIIT group reported significantly lower RPE than the HIIT group (p < 0.05). In conclusion, compared to HIIT, BFR-MIIT can achieve equivalent improvements in aerobic capacity at lower training intensities and perceived exertion while yielding better improvements in lower extremity performance.